2012
DOI: 10.1063/1.4729556
|View full text |Cite
|
Sign up to set email alerts
|

The influence of substrate morphology on thickness uniformity and unintentional doping of epitaxial graphene on SiC

Abstract: A pivotal issue for the fabrication of electronic devices on epitaxial graphene on SiC is controlling the number of layers and reducing localized thickness inhomogeneities. Of equal importance is to understand what governs the unintentional doping of the graphene from the substrate. The influence of substrate surface topography on these two issues was studied by work function measurements and local surface potential mapping. The carrier concentration and the uniformity of epitaxial graphene samples grown under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 30 publications
4
53
0
Order By: Relevance
“…As previously described in Section 2.3, graphene on SiC(0001) is intrinsically n-doped [32,57,100]. Additionally, the high humidity level [7,25,80], gasses [87] and photochemicals [17,101] attached to the surface of graphene act as sources of extrinsic doping, providing both n-and p-type dopants (Sections 2.2 and 2.3).…”
Section: Influence Of External Conditionsmentioning
confidence: 95%
See 1 more Smart Citation
“…As previously described in Section 2.3, graphene on SiC(0001) is intrinsically n-doped [32,57,100]. Additionally, the high humidity level [7,25,80], gasses [87] and photochemicals [17,101] attached to the surface of graphene act as sources of extrinsic doping, providing both n-and p-type dopants (Sections 2.2 and 2.3).…”
Section: Influence Of External Conditionsmentioning
confidence: 95%
“…Nevertheless, domains of different layer thickness have an ‗intrinsic' roughness [56], which is likely to influence the graphene-IFL-substrate interaction. Substrate steps also influence the charge interaction, where the terrace width and height are both dependent on the exact growth conditions [57] and the miscut of the original SiC crystal [58]. It was shown that when the graphene passes over a terrace edge, a detachment of the graphene from the substrate is possible leading to an abrupt change in local doping [59], which can be seen with KPFM and EFM as a change in the potential ( Figure 2).…”
Section: Effects Of Structural Defects and Strainmentioning
confidence: 98%
“…Substrate characteristics, such as terrace width in SiC, can also be a dominating factor in determining the unintentional doping of monolayers [78]. Unique work function variations of graphene line defects, grain boundaries, standing-collapsed wrinkles, and folded wrinkles could be clearly identified by high-resolution KPFM (Figure 3a-c).…”
Section: Electrical Modesmentioning
confidence: 99%
“…[1,2,[6][7][8] However, growth kinetics of graphene on SiC invariably leads to formation and uncontrolled reconstruction of steps at the substrate surface and successive formation of terraces. [9,10] In principle, graphene layers nucleate at the step edges and once monolayer grows on the SiC surface, no more Si can sublimate leading to a self-limiting growth process. [7,11] Nevertheless, in practice, new graphene domains can still grow at the SiC-graphene interface even if the surface is already covered with graphene.…”
Section: Introductionmentioning
confidence: 99%